Digital Technology Platforms for Community-Based Hypertension Management: A Bibliometric Analysis - Sudarman Sudarman; Regidor III Dioso; Hafizah Che Hassan (STIKep PPNI Jawa Barat, 2026)
Background: Hypertension remains a major global health challenge requiring effective and sustainable long-term management. The rapid advancement of digital health technologies has introduced new opportunities to enhance blood pressure control, patient adherence, and community-based care delivery. Objective: This study aimed to analyze global research trends on digital technology platforms for community-based hypertension management using a bibliometric approach, and to identify key research themes, collaboration patterns, and emerging gaps. Methods: A bibliometric analysis was conducted using data retrieved from the Dimensions.ai database for publications between 2021 and 2025. Study selection followed PRISMA guidelines with predefined inclusion and exclusion criteria. Data were analyzed using VOSviewer to visualize keyword co-occurrence, collaboration networks, and thematic evolution through network, overlay, and density mapping. Results: Of 14,455 identified records, 3,371 articles met the inclusion criteria. The analysis identified 161 key items grouped into five thematic clusters, with a total link strength of 19,847. Findings demonstrate a clear shift in research focus from conventional clinical treatment approaches toward the integration of digital health technologies, including telemonitoring, self-management systems, patient engagement tools, and artificial intelligence in community-based hypertension care. Conclusions: Digital technology platforms are increasingly central to community-based hypertension management, particularly in improving blood pressure control, medication adherence, and healthcare accessibility. However, critical gaps remain regarding long-term effectiveness, interoperability, and data privacy. Future research should prioritize sustainable implementation and integration within health systems to maximize clinical and public health impact